Bleeding Rate After Tooth Extraction in Patients Under Oral Anticoagulant Therapy. Issue 5 (July 2016) - Dudek, Damian; Marchionni, Saverio; Gabriele, Mario; Iurlaro, Antonio; Helewski, Krzysztof; Toti, Paolo; Gelpi, Federico; Bertossi, Dario; Barone, Antonio
Abstract : Objectives: The aim of this single-cohort prospective study was to evaluate the risk of adverse outcomes after tooth extraction in patients suffering from cardiovascular disorders and under oral anticoagulant therapy with an international normalized ratio within the value of 3.0. Methods: Two hundred ninety-three patients (mean age of 58.7 years) were enrolled and 560 tooth extractions were performed. Fresh extraction sockets were treated with collagen tablets and sutures. The risk of increased bleeding rate was evaluated for type of drug therapy (acenocoumarol or warfarin), type of cardiovascular diseases, and number of tooth extractions. Level of significance was set at 0.05. Results: The overall bleeding event rate was 6.8%. Among patients who had bleeding events, 4 suffered from valvular disorders, whereas 11 suffered from arrhythmias (8) or cardiomyopathies (3). The remaining 5 patients had a history of cardiomyopathy and arrhythmia. The bleeding events in patients who had more than 2 tooth extractions were significantly higher than those observed in patients who had only 1 tooth extraction ( P  <0.05). Conclusion: Patients who received more than 2 tooth extractions, who were under treatment with acenocoumarol, and who suffered from multiple cardiovascular diseases were at high risk for bleeding events.